Prospects of using chondroprotectors for the treatment of pulmonary pathology - I. Yu. Torshin; O. A. Gromova; A. G. Chuchalin (Фармакоэкономика, 2022)
Background. The complex mechanisms of action of chondroitin sulfate (CS) and glucosamine sulfate (GS) at the molecular level make it possible to assert the applicability of the corresponding drugs far beyond chondroprotection. Inhibition of proinflammatory mechanisms (NF-κB, activation of toll-receptors, increased levels of cytokines, degranulation of mast cells, etc.) by CS and GS provide the prospects for their use to inhibit inflammation in the respiratory tracts, allergic processes and to enhance the effects of glucocorticoids.Objective: to systemize data on the effects of chondroitin sulfate and glucosamine sulfate on pathophysiological processes in pulmonary pathology.Material and methods. Using the methods of the theory of text topological analysis an intellectual analysis of 1273 publications on fundamental and clinical studies of the relationship of CS and GS with lung function was carried out. The search was performed by a key query “(glucosamine OR chondroitin) AND (lung OR lungs OR pulmonary OR pulmonology)” in the Pubmed/MEDLINE database. As a result, 59 informative biomedical terms were identified.Results. The chemoproteomic study of CS and GS showed that their intake promoted an increase in the expression of 19 antitumor proteins and a decrease in the expression of 25 pro-inflammatory proteins involved in lung function. CS and GS can be used in the complex therapy of infectious diseases of the lungs, with fibrotic changes in the respiratory tracts and, as well, help to reduce the risk of neoplastic diseases of the lungs.Conclusion. The results of this analysis allow us to assert the promising nature of the use of CS and GS in several neoplastic diseases of the lungs, as well as the high safety of drugs based on pharmaceutical standardized forms of CS and GS in terms of lung function.